PENINGKATAN KEMAMPUAN MAHASISWA MENULIS CERITA ANAK MELALUI STRATEGI MENULIS TERBIMBING - Zubaidah, Enny (LITERA, 2015)
Abstract This action research study aims to improve students' skills in writing children's stories through the guided writing strategy. The research subjects were semester three students of PGSD FIP UNY. The data were collected through a pretest and a posttest in each cycle, interviews, observations, field notes, portfolio, and questionnaires. The data were analyzed using descriptive statistics. The results of the study were as follows. First, the use of the guided writing strategy was capable of improving students' skills in writing children's stories. The learning process was implemented by making the students understand elements of a child's story and language elements through: (a) reading children's stories by other writers, (b) discussing strory reading results by analyzing story elements, (c) retelling the stories that had been read, and (d) writing stories independently. Second, the students' skills in writing children's stories improved in each cycle. Based on the pretest results, no student (0%) had a high level of skills, 7 students (25.9%) had a moderate level of skills, and 20 students (74.1%) had a low level of skills. Based on the posttest results in Cycle 3, 12 students (44%) had a high level of skills, 15 students (56%) had a moderate level of skills, and no student had a low level of skills. Keywords: story writing, schildren's stories, guided writing strategy